(3GdMLIs - (3CMeO Hf ehSi Hf GdYHGS GdJejej, CHh HcQ Hf eLGgO , (B324 (3g` s; (3GdMSf Hf CMeO Hf YHO GdZaGQ GdaGQSqj GdCUd, CHh Ydj, (B377 (3g`s ((3GdYHGS Hf CMeO GdehGSi s)
(3ChdgG (B:s
(3JHJOF ef bhdg JYGdi (B" (3Ef GdefGabjf ai GdOQc GdCSad ef GdfGQ s
(3BNQgG (B:s
(3hJfJgi Edi bhdg JYGdi (B" (3Hd ddg GdCeQ LejYkG (B" s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B8 s
(3eUOQ GbJfGA GdCUd (B:s
(3TgjO Ydi (B(27) s
Keywords: (3GdbQGAGJ hGdJLhjOs